2005
DOI: 10.1038/sj.jhh.1001867
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating concentrations of asymmetric dimethylarginine (ADMA) in white coat hypertension

Abstract: Elevated plasma levels of the endogenous nitric oxide (NO) synthase inhibitor asymmetric dimethylarginine (ADMA) contribute to endothelial dysfunction and seem to be a predictor for cardiovascular mortality. Elevated ADMA plasma concentrations have been demonstrated in patients with hypertension. However, the plasma concentrations of ADMA in white coat hypertension (WCH) has not been previously studied. The aim of this study was to evaluate ADMA in WCH and compare with normotensive (NT) and hypertensive (HT) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
(59 reference statements)
3
17
1
3
Order By: Relevance
“…Intravenous administration of ADMA increased systemic vessel resistance and arterial blood pressure (37 ), and systolic blood pressure has been found to be related to ADMA (25,38 ). These findings, however, have not been confirmed by all studies.…”
Section: Discussioncontrasting
confidence: 45%
“…Intravenous administration of ADMA increased systemic vessel resistance and arterial blood pressure (37 ), and systolic blood pressure has been found to be related to ADMA (25,38 ). These findings, however, have not been confirmed by all studies.…”
Section: Discussioncontrasting
confidence: 45%
“…Homocysteine and asymmetric dimethylarginine levels were examined in two different studies with contradictory results. Pierdomenico found no significant differences in homocysteine levels among WCHT patients and NT patients, whereas Curgunlu et al [42,43] showed significantly higher homocysteine levels in WCHT patients (P < 0.001). Homocysteine levels were significantly higher in SHT patients than in WCHT patients, with P values of 0.0003 and P < 0.001 in the studies performed by Pierdomenico et al [44] and Curgunlu et al [42,43] , respectively.…”
Section: White-coat Hypertension and Target Organ Damagementioning
confidence: 88%
“…Pierdomenico found no significant differences in homocysteine levels among WCHT patients and NT patients, whereas Curgunlu et al [42,43] showed significantly higher homocysteine levels in WCHT patients (P < 0.001). Homocysteine levels were significantly higher in SHT patients than in WCHT patients, with P values of 0.0003 and P < 0.001 in the studies performed by Pierdomenico et al [44] and Curgunlu et al [42,43] , respectively. Regarding inflammation, only one of three WCHT studies on C-reactive protein found a significant difference between the WCHT and NT groups [41,45,46] .…”
Section: White-coat Hypertension and Target Organ Damagementioning
confidence: 88%
“…The correlation between ADMA and NO was stronger in WCH group than in HT. Although NO levels in HT patients were lower than white coat hypertensives and ADMA levels in HT patients were higher than WCHs, the negative correlation of these two parameters were more pronounced in WCH group [5].…”
Section: The Effect Of Nitric Oxidementioning
confidence: 90%